'Cabined, cribbed, confined, bound in' or 'we are not a government poodle': Structure and agency in museums and galleries. (July 2014) - Gray, Clive
Arguments within political science, public administration and public policy about how to both conceptualise and operationalise structure and agency in analysis have tended to operate at the level of ontology – and occasionally at the level of epistemology. This paper argues that development at the methodological level is required to make sense of the complexities of this debate. An analysis of how structure and agency can be applied to the museums policy sector is utilised to demonstrate the importance of linking methodology to epistemology and ontology, and to show the analytical consequences that arise from this.